Salvatore Sciarrino. The Sicilian alchemist composer - Misuraca, Pietro (Interdisciplinary Studies in Musicology, 2018)
Salvatore Sciarrino (Palermo, 1947) began his career in the fervent climate of the six Settimane Internazionali Nuova Musica. Still very young he attracted the attention of the musical world, with his sonorous invention full of startling innovation that was to make him one of the protagonists of the contemporary musical panorama. Sciarrino is today the best-known and most performed Italian composer. His catalogue is a prodigiously large one, and his career is dotted with prestigious prizes and awards. Alchemically transmuting sound, finding new virginity in it has for fifty years been the objective of his music. Timbric experimentation is the goal of his virtuosity. The prevailing use of harmonic sounds and other subversive emission techniques make his sonorous material elusive, incorporeal, particularly close to noise: hence not sounds in the traditional sense, but ghosts and shades of sounds, systematically deprived of the attack and situated in a border zone between the being of the material and its not-being. The sound comes out changed by the osmotic relationship with silence: it is a mysterious epiphany, a “presence” that strives to appear on the surface, living and pulsating almost according to a physiology of its own. Hence it is a music of silences furrowed by minimal sound phenomena, for an “ecology of listening” - an antidote to the noise pollution of consumer society - able to clear perception, to sharpen auditory sensibility and to free the mind of stereotyped stimuli. His music is not concretized in intervallic relations and in harmonic-contrapuntal constructive logics, but in complex articulatory blocks which Sciarrino calls figures. Even though the structural use of timbre becomes a disruptive fact, which brings an upheaval to the perception of pitches and seems to burn up every linguistic residue, in thefigural articulation and in its perceptibility the composer finds a new logic and a new, infallible sense of form. Musical discourse proceeding through complex wholes is mirrored in Sciarrino’s peculiar composition method. For him the layout of a score in traditional notation is preceded by a graphic-visual project (which he calls “flow chart”) allowing synthetic control of the form and highlighting the relationship between construction and space. “Window form” had become a characteristic feature of his composition technique. With this term, borrowed from computer terminology, the composer indicates a formal procedure that mimics the intermittence of the human mind and that he considers typical of the modem and technological era. The gradual recovery of a new singing style is a central problem in his most recent production: psychotic and gasping utterance, messa di voce, glissandos, portamenti, slipping syllabification, incantatory and alienating reiterations avoid all danger of stylistic regression, shaping a new and personal monody, artificial and hallucinatory. The working-out of a personal singing style is Sciarrino’s main conquest in the last years. Hence his fundamental contribution to experiments in contemporary musical theatre and a particular flowering of vocal works that characterizes his most recent creative phase.